Micronutrient regulation of the DNA methylome - Leesang, Tiffany; Lyon, Peter; Pinzone, Joey; Cimmino, Luisa (Frontiers in Epigenetics and Epigenomics, 2024)
The formation, inheritance, and removal of DNA methylation in the genome of mammalian cells is directly regulated by two families of enzymes–DNA methyltransferases (DNMTs) and Ten-Eleven Translocation proteins (TETs). DNMTs generate and maintain the inheritance of 5-methylcytosine (5mC), which is the substrate targeted by the TET enzymes for conversion to 5-hydroxymethylcytosine (5hmC) and its downstream oxidized derivatives. The activity of DNMT and TET is dependent on the availability of micronutrients and metabolite co-factors, including essential vitamins, amino acids, and trace metals, highlighting how DNA methylation levels can be directly enhanced, suppressed, or remodeled via metabolic and nutritional perturbations. Dynamic changes in DNA methylation are required during embryonic development, lineage specification, and maintenance of somatic cell function that can be fine-tuned based on the influence of essential micronutrients. As we age, DNA methylation and hydroxymethylation levels drift in patterning, leading to epigenetic dysregulation and genomic instability that underlies the formation and progression of multiple diseases including cancer. Understanding how DNA methylation can be regulated by micronutrients will have important implications for the maintenance of normal tissue function upon aging, and in the prevention and treatment of diseases for improved health and lifespan.